FORMATION OF POTTERY SCHOOLS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Gurumsarai pottery is world famous for its secret obtained from natural plants. Plants grow in mountain and sub-mountain areas. There are 2 different types of plants: they are called by the names of forty syllables and gulak, and the plants mainly ripen in the beginning of the autumn months. They are collected and then burned. Ashes of burned plants are melted by placing them in a furnace at 900 00 or 1100 00 degrees. The alkali dissolved in the khumdon is crushed and crushed to a fine state with the help of a millstone, and the finished mixture is mixed with water on the surface of the decorated ceramic objects. Glazed ceramics are baked in a steam room after stirring for a certain time